Palladium-catalyzed difunctionalization/dearomatization of N-benzylacrylamides with α-carbonyl alkyl bromides: facile access to azaspirocyclohexadienones. Issue 35 (31st August 2021) - Peng, Chuan-Chong; Wu, Li-Jun; Pi, Shao-Feng
Abstract : An efficient palladium-catalyzed difunctionalization/dearomatization of N -benzylacrylamides with α-carbonyl alkyl bromides for the preparation of azaspirocyclohexadienones has been disclosed. Abstract : An efficient palladium-catalyzed difunctionalization/dearomatization of N -benzylacrylamides with α-carbonyl alkyl bromides as alkyl radical precursors has been described. Various α-carbonyl alkyl bromides, including α-bromoalkyl esters and ketones, reacted smoothly to provide important azaspirocyclohexadienones in moderate to excellent yields. In addition, mechanistic studies suggested that the reaction proceeded via a radical pathway.